Competing risks modeling of length of hospital stay enhances risk-stratification of patient care: application to under-five children hospitalized in Malawi - Stanley, Christopher C.; Zulu, Madalitso; Msuku, Harrison; Phiri, Vincent S.; Kazembe, Lawrence N.; Chinkhumba, Jobiba; Mvalo, Tisungane; Mathanga, Don P. (Frontiers in Epidemiology, 2023)
Introduction: Length of hospital stay (LOS) defined as time from inpatient admission to discharge, death, referral or abscondment is one of key indicators of quality in patient care and management. Reduced LOS lowers health care expenditure and minimizes chances of in-hospital acquired infections. Conventional methods for estimating LOS such as Kaplan-Meier survival curve and the Cox proportional hazards regression for time to discharge cannot account for competing risks such as death, referral and abscondment. This 2 study applied competing-risk methods to investigate factors important for risk-stratifying patients on LOS in order to enhance patient care and management. Methods: This study analyzed data from an ongoing safety surveillance of the malaria vaccine implementation program in Malawi's four district hospitals of Balaka, Machinga, Mchinji and Ntchisi. Children aged 1-59 months who were hospitalized (spending at least one night in hospital) with a medical illness were consecutively enrolled between 1 November 2019 and 31 July 20211 November 2019 -31 July 2021. Sub-distribution-hazard (SDH) ratios for cumulative incidence of discharge were estimated with a Fine-Gray competing risk model.Results: Among the 15,463 children hospitalized, 8,607 (55.7%) were male and 6,856 (44.3%) were female.The median age was 22 months (interquartile range [IQR]: 12-33 moths). The cumulative incidence of discharge was 40% lower among HIV-positive children compared to HIV-negative (sub-distribution-hazard ratio [SDHR]: 0.60; [95% CI: 0.46-0.76]; P <0 .001); lower among children with severe and cerebral malaria (SDHR: 0.94; [95% CI: 0.86-0.97]; P = 0 .04), sepsis or septicemia (SDHR: 0.90; [95% CI: 0.82-0.98]; P = 0 .027), severe anemia related to malaria (SDHR: 0.54; [95% CI: 0.48-0.61]; P <0 .001) and meningitis (SDHR: 0.18; [95% CI: 0.09-0.37]; P <0 .001) when compared to non-severe malaria; and also 39% lower among malnourished children compared to the non-malwell-nourished (SDHR: 0.61; [95% CI: 0.55-0.68]; P <0 .001).Conclusions: This study applied a Fine-Gray competing risk approach to more accurately model LOS as time to discharge where there were significant rates of in-hospital mortality, referrals and abscondment. Patient care and management can be enhanced by risk-stratifying on LOS based children age, HIV status, diagnosis and nutritional status.